Fetal skeletal dysplasias in a tertiary care center: radiology, pathology, and molecular analysis of 112 cases. (26th July 2014) - Barkova, E.; Mohan, U.; Chitayat, D.; Keating, S.; Toi, A.; Frank, J.; Frank, R.; Tomlinson, G.; Glanc, P.
Abstract : Fetal skeletal dysplasias are a heterogeneous group of rare genetic disorders, affecting approximately 2.4–4.5 of 10, 000 births. We performed a retrospective review of the perinatal autopsies conducted between the years 2002–2011 at our center. The study population consisted of fetuses diagnosed with skeletal dysplasia with subsequent termination, stillbirth and live‐born who died shortly after birth. Of the 2002 autopsies performed, 112 (5.6%) were diagnosed with skeletal dysplasia. These 112 cases encompassed 17 of 40 groups of Nosology 2010. The two most common Nosology groups were osteogenesis imperfecta [OI, 27/112 (24%)] and the fibroblast growth factor receptor type 3 (FGFR3) chondrodysplasias [27/112 (24%)]. The most common specific diagnoses were thanatophoric dysplasia (TD) type 1 [20 (17.9%)], and OI type 2 [20 (17.9%)]. The combined radiology, pathology, and genetic investigations and grouping the cases using Nosology 2010 resulted in a specific diagnosis in 96 of 112 cases.